The prevalence of foot-and-mouth disease in Asia - Aslam, Munazza; Alkheraije, Khalid A. (Frontiers in Veterinary Science, 2023)
Foot-and-mouth disease (FMD) is listed among the highly contagious diseases of animals and is endemic throughout the Asian continent. The disease is caused by the Foot-and-mouth disease virus (FMDV) and affects a wide variety of domesticated animals as well as wild ungulates. Clinically, the disease is described as vesicular lesion on the tongue, muzzle, lips, gum, dental pad, interdigital cleft, coronary band, and heel of the foot. Sometimes these lesions give rise to lameness. Mastitis is also caused due to teat lesions. The biochemical test reveals that during FMD infection, there are elevated levels of interleukin-1 (IL-1), tumor necrosis factor-alpha, interferon-gamma (IFN- γ), interleukin-6, serum amyloid A protein, lactoferrin, mannose-binding lectin and monocytes chemo-attractant protein-1 in the serum of infected animal. There is no specific treatment for FMD although some antivirals are given as prophylaxis and antibiotics are given to prevent secondary bacterial infection. This review presents comprehensive data on the prevalence of FMD and serotypes of FMDV that are attributable to the cause of FMD from a regional point of view. It also explains the worldwide dynamics the seven serotypes of FMD and tries to identify epidemiological clusters of FMD in various geographical areas. Furthermore, pathology associated with foot and mouth disease virus along with pathophysiology is discussed. Continent-wide prevalence and diversity patterns of FMD suggest that there is a need of stringent policies and legislation implementation regarding research and development aimed at manufacturing strain-specific vaccination, infection prevention, and control of the disease.